2016
DOI: 10.1177/1741143215578447
|View full text |Cite
|
Sign up to set email alerts
|

Search for Trustful Leadership in Secondary Schools

Abstract: The purpose of this study is to analyse how the access to structures of empowerment by teachers in primary and secondary education impacts on their trust of the headmaster of the school management board. Using the theoretical framework of empowerment and trust in the context of companies, one adapted the constructs of these scales to the reality of primary and secondary schools. A questionnaire was presented to 112 teachers in order to evaluate the impact of empowerment structures on their trust of the leader.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
9
0
2
Order By: Relevance
“…Their study showed perceived parental competence and integrity as significant facets of trustworthiness, often centered on parental understanding of their children's regular routines and the adolescents' preceding behavior. Teachers' trust in their leader (principal) has also been found to be based on integrity, benevolence, and competence (Freire and Fernandes, 2015).…”
Section: Operationalization Of Home-school Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study showed perceived parental competence and integrity as significant facets of trustworthiness, often centered on parental understanding of their children's regular routines and the adolescents' preceding behavior. Teachers' trust in their leader (principal) has also been found to be based on integrity, benevolence, and competence (Freire and Fernandes, 2015).…”
Section: Operationalization Of Home-school Trustmentioning
confidence: 99%
“…It has been studied across numerous disciplines (anthropology, economics, psychology, political science, and sociology) with diverse associated aspects and concepts. In home-school contexts, trust has been examined alongside other variables such as schooling outcomes (Adams and Christenson, 2000;Bower et al, 2011;Adams and Forsyth, 2013;Adams, 2014;Romero, 2015;Kwan, 2016;Musah et al, 2018), communication andpartnership (Tschannen-Moran, 2001;Kikas et al, 2011;Eng et al, 2014;Li et al, 2016;Santiago et al, 2016;Houri et al, 2019), job satisfaction (Van Houtte, 2006;Khany and Tazik, 2015), professional effectiveness (Moye et al, 2005;Lee et al, 2011;Choong et al, 2019;Schwabsky et al, 2019), classroom management (Gregory and Ripski, 2010;Amemiya et al, 2020), organizational culture and behavior (Smith et al, 2001;Hoy and Tarter, 2004;Hoy et al, 2006a;Yeager et al, 2017;Farnsworth et al, 2019), leadership (Zayim and Kondakci, 2014;Freire and Fernandes, 2015;Louis and Murphy, 2017;Yin and Zheng, 2018;Farnsworth et al, 2019;Karacabey et al, 2020), and psychological constructs (Rotenberg et al, 2004;Nam and Chang, 2018) among other variables. Demographic characteristics such as socioeconomic status (Goddard et al, 2009;Janssen et al, 2012), ethnicity…”
Section: Introductionmentioning
confidence: 99%
“…School management is held accountable for setting clear boundaries for teachers' tasks and responsibilities and for setting directions for school development. A school organisation where a lot of rules and agreements are being formalised, and which is mainly organised through top-down control, will decrease a teacher's perceived agency (Priestley et al 2015, Vähäsantanen 2015, Freire and Fernandes 2016. Teachers generally hold the belief that school management is held accountable for the allocation of resources and, subsequently, they take a reactive stance (Smylie and Brownlee-Conyers 1992).…”
Section: Boundaries and Responsibilitiesmentioning
confidence: 99%
“…Teachers generally hold the belief that school management is held accountable for the allocation of resources and, subsequently, they take a reactive stance (Smylie and Brownlee-Conyers 1992). A school organisation in which teachers are granted plentiful opportunities for shared decision-making will increase teachers' options for enacting agency (Freire and Fernandes 2016). When opportunities for teacher decision-making increase, this could occur in the harmonious negotiation of roles and responsibilities.…”
Section: Boundaries and Responsibilitiesmentioning
confidence: 99%
“…The relationship between the psychological empowerment of teachers and the related consequences has been analysed by scientists, but there is a lack of evidence-based research on the mechanism of the formation of teacher psychological empowerment, the factors that promote/determine greater empowerment of teachers. The scholarly literature has mainly regarded relationship between teacher psychological empowerment and the principal as a leader behaviour (Shah 2014;Elmazi 2018;Gkorezis 2016;Freire and Fernandes 2016) ignoring other organisational factors and processes as important for the formation of empowerment. However, the teacher empowering process cannot develop, as stated by Kang et al (2021), inside a vacuum.…”
Section: Introductionmentioning
confidence: 99%